Guidelines for managing process safety risks during organizational change - Wiley eBooks; American Institute of Chemical Engineers. Center for Chemical Process Safety (Hoboken, N.J. : Wiley, 2013)
"Organizational Change Management (OCM) has often been overlooked by regulatory and guideline publications in the past. Documents have historically disregarded the topic, mentioned it in passing, or focused on only a few of its aspects. As a result, major decisions regarding reduction in staffing levels, reorganization of the corporate hierarchy, modifications to shift schedules, or adjustment of personnel responsibilities may often be finalized by individuals or committees who lack the understanding of how these changes may affect the health and safety of their employees or the surrounding community. This book addresses these issues and helps companies bring their OCM systems to the same degree of maturity as other process safety management systems. Topics Include: Corporate Standard for Organizational Change Management, Modification of Working Conditions, Personnel Turnover, Task Allocation Changes, Organizational Hierarchy Changes, and Organizational Policy Changes"--
Front Matter -- Introduction and Scope -- Corporate Standard for Organizational Change Management -- Modification of Working Conditions -- Personnel Changes -- Task Allocation Changes -- Organizational Hierarchy Changes -- Organizational Policy Changes -- Appendix A: Example Tools for Evaluating Organizational Changes -- Appendix B: Example Procedures for Managing Organizational Changes.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Chemical industry -- Safety measures; Chemical industry -- Management; Organizational change -- Health aspects; Industrial safety; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Electronic books